Green Synthesis of Tetragonal YCa2Cu3O7-δ - Nagar, Achala; Mathur, Praveen (Asian Journal of Chemistry, 2011)
The bulk superconducting YCa2Cu3O7-δ compounds have been prepared in a short time of 35 min using a domestic microwave oven operated at 2.45 GHz and 600 W, without any post-heat treatment. Post heat treatment was avoided as the sample was irradiated with microwaves by adjusting long heating cycles. Intermittent regrinding leads to the successful preparation of homogenous tetragonal YCa2Cu3O7-δ which is found to be superconducting at 61.8 K. The analysis is consistent with published data on YCa2Cu3O7-δ oxide superconductor.